Are all renewable energy sources the same? a comparative analysis of public perceptions and preferences for renewable energy types in Southeast Asian cities - del Barrio Alvarez, Daniel; Wang, Nan; Sugiyama, Masahiro; Numata, Masako; Thuy, Truong Dang; Abd Aziz, Azlina; Palanca-Tan, Rosalina; Ze Ya, Aung; Yusuf, Ariel Anshory; Abd. Ghani, Awang Noor; Castillo, Gem; Siyaranamual, Martin Daniel (Springer, 2024)
The realization of a sustainable energy transition in Southeast Asia will require the overcoming of the current high reliance on fossil fuels in the energy mix and the steady and rapid growth in energy demand in the region. To achieve an economically, socially, and environmentally sustainable energy transition in the region, it is vital to utilize all available renewable energy sources to the greatest extent possible. It is therefore essential to gain an understanding of how citizens in each country perceive the available renewables. However, the majority of existing literature in this region has been constrained by a narrow focus on a comparison between fossil and renewable energy. Furthermore, while previous research has predominantly concentrated on single-country analyses, there are significant implications that could be disseminated across ASEAN countries. In light of the aforementioned limitations of existing literature, this paper aims to make a contribution by undertaking a comparative analysis of public preferences for renewable energy sources in eight major urban areas in seven Southeast Asian countries. The findings of this study indicate that, while climate change (or global warming) is perceived as a significant issue, it is often regarded as a secondary concern compared to other environmental issues. This is despite the fact that many of these issues are closely interlinked with and would be exacerbated by climate change. Furthermore, the findings suggest that solar energy is the most preferred renewable source across all urban areas surveyed. In contrast, bioenergy (or biomass) is generally the least preferred source of energy in all cities. There is considerable variation in perceptions of wind, hydro, and geothermal energy, with a high degree of variability between and within countries. These similarities and differences in preferences for renewable energy sources appear to be associated with varying levels of knowledge or familiarity with each source, which is consistent with differing willingness to pay for each source. These findings highlight the necessity for policies that address this apparent lack of understanding of how the transition to a sustainable energy system and each renewable energy technology can help mitigate the impact of environmental problems highlighted in each society.